ESTIMATION OF WATER TRANSPORT FROM OSCILLATIONS OF THE ON-SHORE TELLURIC FIELD GENERATED BY TIDES - Monteiro Santos F.A.; Nolasco R.; Soares A.; Bernardo I.; Dias J.M. (My University, 2007)
On-shore measurements of telluric field oscillations have been used together with electric field acquired in a submarine cable crossing a channel (in Aveiro area) to estimate the water transport through the channel. The on-shore N-S dipole was calibrated by correlating the lunar tidal water transport and the corresponding on-shore motionally tidal electric field. A calibration factor of 7350 m3 s- 1for each mV/km, with motionally induced origin, was estimated. Theoretical polarization ellipses of the electric field with tidal origin and telluric field attenuation during inland propagation agreed very well with observed values. The results showed that it is possible to estimate the water transport from on-shore measurements. © 2007 Elsevier B.V. All rights reserved.
Keywords: ELECTROMAGNETIC; MASS FLUX; MOTIONALLY INDUCED ELECTRIC FIELD; TIDES